Using a priori algorithm for supporting e-commerce system - Ahmad Sharif, Mohammad Nazir; Bahari, Mahadi; Bakri, Aryati; Zakaria, Nor Hidayati (2005)
The Internet technology has brought about a significant impact in doing business. It promotes the new way of doing business by enabling new system such as electronic commerce (e-commerce) to the worldwide users. Currently, the e-commerce system does not only provide electronic transactions like online payment, electronic cart shopping and ordering, and online tracking, but it must also be able to support a good relationship with their customers by providing a creative way in its business operations. It is because of many organizations having to maintain their customers by serving a good customer satisfaction. Lack understanding of the customers will cause an organization loss their customers and then would loss the company profit. This paper demonstrates the development of e-commerce system by focusing on the use of a Priori algorithm as supported feature in our e-commerce system. The feature is included to increase a good customer relationship management for the proposed system. It is hoped the proposed prototype would illustrate some practical ideas on how much advantages can be benefited from the e-commerce system and customer relationship management.